Analisis Rasio Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT. Kimia Farma (PERSERO) Tbk - Yunita Martina; Wagini wagini wagini; Nenden Restu Hidayah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
One of the tools to assess financial performance is profitability ratio analysis which aims to measure the overall management effectiveness which is indicated by the size of the level of profit obtained. The better the profitability ratio, the better the profitability of a company. The purpose of this study was to determine the profitability ratios to assess financial performance at PT. Kimia Farma (Persero) Tbk in 2010-2020. The data collection method uses documentation and literature study, and the analytical method used is quantitative analysis using profitability ratio analysis, namely Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE). The results showed that the Gross Profit Margin (GPM) in 2010 was 28.41% based on the criteria for assessing this situation in good condition. In the following years GPM has always increased so that the company is in very good condition. With that we can see that there is an increase in profits obtained. Net Profit Margin (NPM) in 2010 to 2018 was always in a good position, in 2019 and 2020 there was a very far decline to <1% until this position resulted in a bad condition. Return On Assets (ROA) in 2010 to 2018 there has always been a decline in the level of this ratio but even so this ratio is still classified as very good, in 2019 and 2020 this ratio has decreased very much, namely <1% causing this ratio to be in a state of disrepair. good. Return On Equity (ROE) in 2010 to 2018 this ratio experienced a change in the increase or decrease in the level of the ratio >10% so this ratio was fairly good, but in 2019 and 2020 there was a very large decline in the ratio level to <1% this caused this ratio in bad shape in the last two years.